1986
DOI: 10.1159/000206049
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Plasmacytoma of the Bone in a Case of Hodgkin’s Disease

Abstract: This report describes a case of solitary plasmacytoma of the bone which occurred in a 35-year-old male 3 years after mantle field irradiation for Hodgkin’s disease, nodular sclerosing, stage IA. The possible significance of this rare association is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This notion was echoed in the case reports of Gherlinzoni and Ibarrola. 15,19 In this vain, the more common course of HL followed by myeloma seems to correlate with the maturation of a B-cell neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…This notion was echoed in the case reports of Gherlinzoni and Ibarrola. 15,19 In this vain, the more common course of HL followed by myeloma seems to correlate with the maturation of a B-cell neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge no cases with MM preceding HD have been reported. Some patients have developed plasmocytoma [10,20], MM [1,3,11] or monotypic plasma cell proliferations of unknown significance [9] after HD therapy These proliferations were attributed to the carcinogenic risks associated with the therapy. There have been also some reports of simultaneous occurrence of HD and paraproteinaemia of uncertain significance [5,16,26,28], including one of a case with bone marrow plasmocytosis [26] and another with monotypic plasma cell proliferation in a lymph node [28].…”
Section: Discussionmentioning
confidence: 99%
“…In China, the annual incidence of MM is ~1 case/100,000 individuals (9,10). The simultaneous occurrence of two types of lymphatic system malignant tumor within the same patient is extremely rare, with an occurrence rate of 1.4-6.5 cases/1,000,000 individuals (15).…”
Section: A B C D F Ementioning
confidence: 99%
“…Previous studies have also reported the simultaneous occurrence of HL and chronic lymphocytic leukemia, peripheral T-cell lymphoma or diffuse large B-cell lymphoma (16)(17)(18). Furthermore, certain patients have developed plasmocytoma (15,19), MM (20,21) or monotypic plasma cell proliferations of unknown significance (22) following therapy for HL; it is unclear whether such secondary tumors are associated with the side effects of the first cancer treatment. Hasskarl et al (23) suggested that MM is associated with hematological neoplasms.…”
Section: A B C D F Ementioning
confidence: 99%